PENGARUH PEMAHAMAN FATWA MUI TENTANG PERLINDUNGAN HKI TERHADAP PERILAKU PELANGGARAN HAK CIPTA DIKALANGAN MAHASISWA YOGYAKARTA - Aris Badaruddin Thoha (LPPM STMIK El Rahma Yogyakarta, 2019)
Copyright infringement, especially the use of illegal computer (software) programs, is common in Indonesia. According to the BSA report in the 2011 Global Software Piracy Study which was released on May 15, 2012, found 59 percent of computer users in Indonesia claimed to do software piracy. The Indonesian Ulama Council as one of the Islamic religious institutions in the State of Indonesia has issued a fatwa number 1 / MUNAS VII / MUI / 15/2005 concerning the Protection of Intellectual Property Rights, which contains several considerations, the legal basis and the mafsadat caused. This study takes the scope of copyright violations of computer programs in the world of education that are loaded with the use of various computer programs. The education world should be free from this copyright infringement behavior. To find out the legal reality in the community in this case the academic community, this study uses a type of quantitative research or survey research with a quantitative data analysis approach. This study takes direct data with a questionnaire about the perspective of students in Yogyakarta about the behavior of using computer programs that violate copyright and how the governing law can affect the community. The results of this study are understanding of FATWA MUI No. 1/MUNASVII/ MUI/15/2005 concerning IPR Protection does not affect IPR violation behavior.